Diatoms as bioindicators for health assessments of ephemeral freshwater ecosystems: A comprehensive review - Taurozzi Davide; Cesarini Giulia; Scalici Massimiliano (Ecological Indicators, 2024)
Ephemeral waters (EW) are sensitive and vulnerable ecosystems that, although the numerous ecosystem services provided, are poorly investigated and properly managed. Diatoms represent an important biological model largely used in aquatic permanent habitats but underused in ephemeral waters. The aim of this review is to address the knowledge gap, examining the current state of knowledge regarding the health of EW, with a focus on diatoms as bioindicators, specially (i) presenting research trends on EW ecosystem types investigated (ii) analysing the methodological approach, (iii) providing the influence of abiotic factors on the diatom assemblages in EW. A bibliographic search yielded a total of 512 papers. After removing duplicate records, 118 were eliminated. The screening of abstracts resulted in the selection of 48 articles on diatoms and EW since 1982. To avoid discrepancy between terminology we decided to classify the EW found in 3 different categories: Intermittent Running Waters (IRW: rivers, streams, creek, springs), Temporary Large Wetlands (TLW: wetlands, lakes, lagoons) and Temporary Small Waters (TSW: ponds, pools, ventaroles, ditches, thermal waters, troughs, pans). Studies are reported in all continents including Antarctic. IRW are the most investigated ecosystem (n = 683), followed by TSW (239) and TLW (96). Furthermore, studies were mainly conducted on sites located below 1000 m a.s.l. of altitude (n = 27). Studies mainly focus on epilithic diatoms (52 %). Electrical conductivity (80 %), pH (77 %) and water temperature (75 %) are the principal physical-chemical parameters considered. Moreover, electrical conductivity, pH, temperature, nitrate and nitrite resulted the best diatom community drivers. Future research is encouraged (1) to achieve a standardised protocol for monitoring EW using diatoms, (2) to focus on conservation projects for high-altitude temporary waters, and (3) to investigate the main driving forces influencing diatom diversity on EW.